2013
DOI: 10.12775/dem.2013.007
|View full text |Cite
|
Sign up to set email alerts
|

Analiza β-konwergencji. Od tradycyjnego modelu przekrojowego do dynamicznego modelu panelowego

Abstract: The aim of the paper is to discuss the course of development of methodology of economic convergence analyses, which points up the necessity of taking into consideration spatial connections among regions in regional growth models. It presents empirical models of β-convergence concerning the economic growth of European regions using various methodological conceptions. In the paper the models offered by spatial econometrics are recommended. The empirical data refer to per capita GDP across the European Union regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Despite the existence of what was called the "growth regression industry", in which there are a considerable amount of studies on the subject and a great variety of theories and indicators [17], the empirical evidence continues to be inconclusive [18][19][20] and although there are studies that relate the economic structure with productivity [21,22], there are few studies that link this productive structure with the processes of beta-convergence in productivity [23]. Criticisms of convergence studies have also indicated that the convergence found in econometric models could even be present when regional dispersion was not decreasing [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of what was called the "growth regression industry", in which there are a considerable amount of studies on the subject and a great variety of theories and indicators [17], the empirical evidence continues to be inconclusive [18][19][20] and although there are studies that relate the economic structure with productivity [21,22], there are few studies that link this productive structure with the processes of beta-convergence in productivity [23]. Criticisms of convergence studies have also indicated that the convergence found in econometric models could even be present when regional dispersion was not decreasing [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Nie jest to miejsce, by bliżej charakteryzować system nomenklaturowy jako taki 10 . Tworzył on wielopiętrowe mechanizmy rekrutacji i awansu, z grubsza odpowiadające wielopiętrowej strukturze hierarchicznej PZPR.…”
Section: Kontekst Formalno-organizacyjny -Gdańska Nomenklatura Partyjna a śRodowisko Dziennikarskieunclassified